Strategies for facilitating the delivery of cluster randomized trials in hospitals: A study informed by the CFIR-ERIC matching tool. (August 2021) - Weir, Arielle; Presseau, Justin; Kitto, Simon; Colman, Ian; Hatcher, Simon
Background: Recruitment and engagement of clusters in a cluster randomized controlled trial can sometimes prove challenging. Identification of successful or unsuccessful strategies may be beneficial in guiding future researchers in conducting their cluster randomized controlled trial. This study aimed to identify strategies that could be used to facilitate the delivery of cluster randomized controlled trials in hospitals. Methods: The study employed the Consolidated Framework for Implementation Research–Expert Recommendations for Implementing Change matching tool. The barriers and enablers to cluster randomized controlled trial conduct identified in our previously conducted studies served as a means of determinant identification for the conduct of cluster randomized controlled trials. These determinants were mapped to Consolidated Framework for Implementation Research constructs and then matched to Expert Recommendations for Implementing Change compilation strategies using the Consolidated Framework for Implementation Research–Expert Recommendations for Implementing Change matching tool. Results: The Expert Recommendations for Implementing Change strategies matched to at least one determinant Consolidated Framework for Implementation Research construct were as follows: (1) 'Identify and prepare champions', (2) 'Conduct local needs assessment', (3) 'Conduct educational meetings', (4) 'Inform local opinion leaders', (5) 'Build a coalition', (6) 'Promote adaptability', (7) 'Develop a formal implementation blueprint', (8) 'Involve patients/consumers and family members', (9) 'Obtain and use patients/consumers and family feedback', (10) 'Develop educational materials', (11) 'Promote network weaving', (12) 'Distribute educational materials', (13) 'Access new funding' and (14) 'Develop academic partnerships'. Conclusion: This study was intended as a step in the research agenda aimed at facilitating cluster randomized controlled trial delivery in hospitals and can act as a resource for future researchers when planning their cluster randomized controlled trial, with the expectation that the strategies identified here will be tailored to each context.